Stable variety selection over locations and recommendations for rose-scented geranium (Pelargonium graveolens L' Herit. ex Aiton.). Issue 1 (2nd January 2018) - Singh, Ved R.; Verma, Ram S.; Upadhyay, Rakesh K.; Lal, Raj K.; Padalia, Rajendra C.; Chanotiya, Chandan S.; Nilofer
Abstract: Objective : In this study, productivity and essential oil quality of rose-scented geranium (Pelargonium graveolens L' Herit. ex Aiton.) varieties, namely CIMAP Bio-G-171, CIM-Pawan and Bourbon were assessed and compared in two locations of north India.Methods : A field experiment was conducted to evaluate the productivity, while the chemical composition of the essential oils was assessed by GC-FID and GC-MS.Result : Yields of fresh leaves and essential oil from CIMAP Bio-G-171 were significantly higher (173.64–174.42 q h -1 and 69.93–79.06 l h -1 ) than those of CIM-Pawan (158.08–160.56 q h -1 and 55.57–64.46 l h -1 ) and Bourbon (133.34–139.33 q h -1 and 44.19–48.38 l h -1 ). Major constituents of the oils were citronellol (20.9–39.5%), geraniol (10.9–26.5%), linalool (2.9–14.2%), isomenthone (7.4–9.4%), citronellyl formate (5.5–9.1%) and 10-epi-γ-eudesmol (5.2–9.0%).Conclusion : The essential oil yields and chemical compositions were substantially influenced by variety and location of growing. The variety CIMAP Bio-G-171 showed improvement up to 58.2–63.4% and 22.6–25.8% in essential oil productivity over the existing prevalent varieties, Bourbon and CIM-Pawan, respectively.